Strategic Planning and Organisational Performance in Higher Education: A Quantitative Analysis of the University for Development Studies, Ghana - Abdul-Rahaman, Alhassan (Advances in Social Sciences Research Journal, 2026)
This study examines how strategic planning practices affect organisational performance at the University for Development Studies (UDS), Ghana. Drawing on existing debates that question the impact of formal planning in public higher education, this study investigates four strategic planning dimensions: environmental scanning, management participation, planning formality, and strategic techniques, and their relationship with financial and non-financial performance. Quantitative data were collected from the academic and administrative staff at UDS (n = 250) using a structured questionnaire. Reliability and validity were confirmed (Cronbach’s alpha > .70), and the data were analysed using Pearson’s correlation and multiple regression. The results indicate that strategic planning has a statistically significant positive effect on financial performance (R² = 0.49, p < 0.001), with strategic techniques exerting the strongest influence (β = 0.60, p < 0.001). The effect on non-financial performance is also significant, albeit weaker (R² = 0.23, p < 0.01), primarily driven by environmental scanning (β = 0.46, p < 0.001). These findings highlight the importance of formal strategic planning in improving university outcomes. The implications include a recommendation for policy frameworks to strengthen strategic planning processes in Ghanaian higher education. Limitations are related to the cross-sectional design, suggesting that longitudinal studies are needed to capture causality over time.